Atypical Presentation of Small Bowel Crohn’s Disease: Case Report of Musculoskeletal and Hepatic Complications Without Gastrointestinal Symptoms - Chen Y; Wang F; Xu L; Ke Q; Ji S; Mao J; Jia X; Lai C; Dai S (Journal of Inflammation Research)
Yiyi Chen,1,2 Fei Wang,1,2 Lingna Xu,1,2 Qinbing Ke,3 Shujuan Ji,4 Jie Mao,5 Xiya Jia,1,2 Chuanxi Lai,1,2 Sheng Dai1,2 1Department of Colorectal Surgery, Sir Run Run Shaw Hospital, College of Medicine, Zhejiang University, Hangzhou, Zhejiang, 310016, People’s Republic of China; 2Provincial Key Laboratory of Precise Diagnosis and Treatment of Abdominal Infection, Sir Run Run Shaw Hospital, School of Medicine, Zhejiang University, Hangzhou, Zhejiang, 310016, People’s Republic of China; 3Department of Radiology, Sir Run Run Shaw Hospital, College of Medicine, Zhejiang University, Hangzhou, Zhejiang, 310016, People’s Republic of China; 4Department of Infectious Diseases, Sir Run Run Shaw Hospital, College of Medicine, Zhejiang University, Hangzhou, Zhejiang, 310016, People’s Republic of China; 5Department of Pathology, Sir Run Run Shaw Hospital, College of Medicine, Zhejiang University, Hangzhou, Zhejiang, 310016, People’s Republic of ChinaCorrespondence: Sheng Dai, Email daimd@zju.edu.cnAbstract: Herein, we described a case of small bowel Crohn’s disease with recurrent, unexplained fevers, pain in the right lower back, hip, and groin area over 20 months. The patient did not present any gastrointestinal symptoms and colonoscopy showed no abnormalities. Imaging revealed a liver abscess and multiple lesions with pneumatosis in the muscles of the right lower back region. Initially, disseminated infection was suspected and the antibiotics was administered without success. Subsequently, Magnetic resonance (MR) enterography suggested the possibility of a small bowel fistula which was confirmed during exploratory laparotomy. Inflammation was prominent in a 27-cm segment starting from 30-cm proximal to the ileocecal junction. The segment was resected and pathological examination confirmed Crohn’s disease. Postoperatively, mesalazine was administered, but showed limited efficacy. After modifying the treatment plan to infliximab and azathioprine, the patient was symptom-free and no obvious inflammation was found in the colonoscopy reexamination.Keywords: small bowel Crohn’s disease, extraintestinal manifestations, inflammatory bowel disease, liver abscesses